Plasmonic light harvesting of dye sensitized solar cells by Au-nanoparticle loaded TiO2 nanofibers - Naphade, Rounak A.; Tathavadekar, Mukta; Jog, Jyoti P.; Agarkar, Shruti; Ogale, Satishchandra (Journal of Materials Chemistry A, 2014)
We report a significant enhancement in the performance of dye sensitized solar cells by using in situ Au nanoparticle (Au NP) loaded TiO2 nanofibers (Au: TiO2 NFs) as the light harvesting (LH) layer as compared to the use of only TiO2 nanofibers (NFs) as the LH layer. The Au NP: TiO2 nanofibers are prepared by electro-spinning of a precursor mixture whereby nanostructured porous TiO2 nanofibers are formed and get in situ loaded with only 4-5 nm AuNPs. The as-synthesized nanofibers are characterized by X-ray diffraction, Raman, photoluminescence (PL) and Mott-Schottky analyses. The presence of gold nanoparticles shows considerable improvements in light harvesting and the electrochemical properties of TiO2 nanofibers. A remarkable enhancement in the efficiency by 25% is achieved with the AuNF LH layer as compared to 12% with the NF layer, over the value without any light harvesting layer. The IPCE and impedance analyses reveal commensurate improvements. The impedance study shows a decrease in the transport resistance (R-TiO2) and an increment in the chemical capacitance and life time of the solar cell. Systematic analyses of the optical properties suggest that the enhanced light harvesting by Au NP loaded TiO2 nanofibers is caused by the role of plasmon-polariton modes at the distributed nanoscale Schottky junctions in the Au: TiO2 nanofibers.